INCIDENCE OF ENDOMETRIAL HYPERPLASIA IN 100 CASES PRESENTING WITH POLYMENORRHAGIA/MENORRHAGIA IN PERIMENUPAUSAL WOMEN - Takreem, Amera; Danish, Nargis; Razaq, Sadia (Journal of Ayub Medical College Abbottabad, 2009)
Background: To study the Incidence of endometrial hyperplasia in perimenupausal women presenting with polymenorrhagia/menorrhagia. This observational study was conducted at Gynae '˜B' unit of Khyber Teaching Hospital Peshawar from January 2000 to December 2001. Methods: One hundred consecutive patients who presented at Gynaecology OPD with Polymenorrhagia/ Menorrhagia were registered and incidence of endometrial hyperplasia evaluated in them. All women were above 45 years of age. Post-menopausal bleeding cases were excluded from the study. Results: Out of 100 patients, 15 patients were found to have endometrial hyperplasia, 10 patients (66.6%) simple cystic hyperplasia, 3 patients (20.0%) had adenomotous hyperplasia, 2 patients (13.3%) had atypical hyperplasia, 8 patients (53.3%) with menorrhagia, 1 (6.6%) with polymenorrhagia, and 6 patients (40.0%) with polymenorrhoea. Duration of symptoms was from 4 months to 1 year. Thirteen (86.6%) patients were treated medically, 5 patients (33.33%) needed surgical treatment following medical treatment, 2 patients (13.3%) underwent Total Abdominal Hysterectomy (TAH) and Bilateral Salpingooophorectomy (BSO) who were 51-53 years of age with atypical hyperplasia. Conclusion: endometrial hyperplasia is a pre-malignant condition; if treated in time, incidence can be reduced and early treatment can increase life expectancy and quality in women over age of 45 years. Keyword: Menorrhagia, Polymenorrhagia, Endometrial hyperplasia, Transvaginal Ultrasound, TVS